2020
DOI: 10.1177/1548051820931243
|View full text |Cite
|
Sign up to set email alerts
|

Who Might Support a Tyrant? An Exploration of Links Between Adolescent Family Conflict and Endorsement of Tyrannical Implicit Leadership Theories

Abstract: This research takes an exploratory approach to shed light on the paradox that negative leader characteristics, such as pushy, obnoxious, and manipulative, appeal to some individuals. We employ social learning theory to argue how parents can model conflict for their adolescents, which may shape implicit leadership theories later in life. Spanning 21 years, this longitudinal study examines adolescent family environment and parents’ gender attitudes as antecedents of adult tyrannical implicit leadership theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…We know that 10- and 11-year-old children prefer democratic leadership above autocratic and noninterventionist forms of leadership (White & Lippitt, 1960). Walker et al (2020) found that adults who lived their adolescence in conflict-infused and achievement-focused family environments showed a higher tendency to factor tyranny as an ideal characteristic in a leader. In contrast, adults who lived adolescence in intellectually stimulating family environments were less inclined to endorse tyranny in their ILTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that 10- and 11-year-old children prefer democratic leadership above autocratic and noninterventionist forms of leadership (White & Lippitt, 1960). Walker et al (2020) found that adults who lived their adolescence in conflict-infused and achievement-focused family environments showed a higher tendency to factor tyranny as an ideal characteristic in a leader. In contrast, adults who lived adolescence in intellectually stimulating family environments were less inclined to endorse tyranny in their ILTs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, adults who lived adolescence in intellectually stimulating family environments were less inclined to endorse tyranny in their ILTs. These effects on the emergence of children’s ILTs are amplified by parents’ egalitarian attitudes (Walker et al, 2020). Such results illustrate one process by which the development of children’s ILTs might bifurcate to produce the antiprototypes revealed by Epitropaki and Martin (2004) in adult ILTs.…”
Section: Discussionmentioning
confidence: 99%
“…The leaders’ aggressive control, lack of consideration and demeaning behaviour can lead to a hostile work environment. This can instigate feelings of fear, anxiety and stress among employees, fostering psychological distress (Walker et al , 2020).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…For example, narcissists are seen as charming and confident on first encounter, while their exploitative and manipulative side only shows over time, leading to a delay in negative effect on others (Paulhus, 1998). In fact, leaders with socially undesirable characteristics may successfully attract a crowd of admirers (Judge et al, 2009; Kets de Vries, 2006; Walker et al, 2020). Notably, 33% of respondents endorsed leader profiles that were higher on the dimension of leader tyranny than the prototypical, socially desirable leader profile (e.g., leaders who are sensitive, intelligent, and dedicated; Foti et al, 2012).…”
Section: Literature On Destructive Leadershipmentioning
confidence: 99%